Influence of Firm Size and Profitability on Sustainability Report Disclosure in Technology Sector Firms 2022–2024 - St.Magfira Sri Rahmadahani; Dwi Andriani Putri; Aini Maqfirah; Muchriana Muchran (www.amertainstitute.com, 2025)
This study examines the influence of firm size and profitability on sustainability report disclosure among Indonesian technology firms listed on the Indonesia Stock Exchange (BEI) from 2022 to 2024, utilizing the Global Reporting Initiative (GRI) 2021 Standards. Despite regulatory mandates like POJK No. 51/POJK.03/2017, disclosure levels vary significantly in the technology sector, a key driver of Indonesia’s digital economy. Employing a quantitative causal-comparative approach, the study analyzes data from five firms in the diversified digital and investment subsector, yielding 15 observations. Firm size is measured by the natural logarithm of total assets, and profitability by Return on Assets (ROA). Multiple linear regression results indicate a significant model (F = 4.517, p = 0.034, R² = 0.430), explaining 43% of disclosure variation. Firm size shows a positive but insignificant effect (β = 0.017, p = 0.139), suggesting size alone does not drive disclosure. Profitability exhibits a marginally significant positive effect at the 10% level (β = 0.052, p = 0.086), indicating profitable firms tend to disclose more to enhance stakeholder trust. The findings align with legitimacy and stakeholder theories, contributing to literature on technology sector disclosure and offering insights for firms and regulators to improve transparency. Limitations include a small sample size and exclusion of other variables like governance.